Exact boundary synchronization for a coupled system of 1-D wave equations. (7th April 2014) - Li, Tatsien; Rao, Bopeng; Hu, Long
<x content-type="archive" xml:space="preserve">Abstract</x> Several kinds of exact synchronizations and the generalized exact synchronization are introduced for a coupled system of 1-D wave equations with various boundary conditions and we show that these synchronizations can be realized by means of some boundary controls.